TARDI VARISCAN DEFORMATION IN THE IBERIAN PENINSULA; A LATE FEATURE IN THE LAURASIA-GONDWANA DEXTRAL COLLISION - Dias, Rui (2016)
The Late Variscan deformation event in Iberia, is characterized by an intraplate deformation regime induced by the oblique collision between Laurentia and Gondwan. This episode in Iberia is characterized by NNE-SSW strike-slip faults, which are considered by the classic works as sinistral strike-slips. However, the absence of Mesozoic formations constraining the age of this sinistral kinematics, led some authors to consider it as the result of Alpine reworking. Structural studies in Almograve and Ponta Ruiva sectors (SW Portugal), not only shows that NNE-SSW faults presents a clear sinistral kinematics and are occasionally associated with E-W dextral shears, but also that this kinematics is related to the late deformation episodes of Variscan Orogeny. In Almograve sector, the late Variscan structures are characterized by NNE-SSW sinistral kink-bands, spatially associated with E-W dextral faults. These structures are contemporaneous and affect the previously deformed Carboniferous units. The Ponta Ruiva Sector constrains the age of deformation because the E-W dextral shears affect the Late Carboniferous (late Moscovian) units, but not the overlying Triassic series. The new exposed data shows that the NNE-SSW and the E-W faults are dynamically associated and results from the same deformation event. The NNE-SSW sinistral faults could be considered as second order dominoes structures related with first order E-W dextral shears, related with Laurasia-Gondwana collision during Late Carboniferous-Permian Times.